Genome Sequences of Gordonia Phages Hotorobo, Woes, and Monty - Pope, Welkin H. (Genome Announc, 2016)
Hotorobo, Woes, and Monty are newly isolated bacteriophages of Gordonia terrae 3612. The three phages are related, and their genomes are similarly sized (76,972 bp, 73,752 bp, and 75,680 bp for Hotorobo, Woes, and Monty, respectively) and organized. They have extremely long tails and among the longest tape measure protein genes described to date.